The Effect of Audit Fees, Audit Tenure, and Gender on Audit Quality in Consumer Goods Companies Listed on the Indonesian Stock Exchange (2020–2024) - Dwi Dinda Nur’arifah; Dwi Saraswati; Tia Novira Sucipto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of Audit Fee, Audit Tenure, and Gender on Audit Quality of Consumer Goods Industry Companies Listed on the Indonesia Stock Exchange for the 2020-2024 Period. Data is taken from www.idx.co.id. The population in this study was 29 companies with a sample of 48 companies. Sampling and determination of sample size in this study were carried out using a purposive sampling method, selecting 34 consumer goods sector manufacturing companies that met the criteria as samples. This research approach uses logistic regression analysis of data processed with the SPSS 23 application. Data from this study uses secondary data in the form of Company financial reports officially published by the Indonesia Stock Exchange (IDX). Based on the results of the study, it can be concluded that the Audit Fee variable has a positive effect on audit quality, Audit Tenure has no effect on Audit Quality, Gender has a positive effect on audit quality, simultaneously Audit Fee, Audit Tenure and Gender affect audit quality. Only 44.3% of the dependent variable can be explained by the variability of the independent variables, while the remaining 55.7% is explained by other variables not used in this study.